The Language of Design Theory and Computation - Dong, Andy An-Si (Springer London : Imprint: Springer, 2009)
The Language of Design: Theory and Computation articulates the theory that there is a language of design. This theory claims that any language of design consists of a set of symbols, a set of relations between the symbols, features that key the expressiveness of symbols, and a set of reality producing information processing behaviors acting on the language. Drawing upon insights from computational language processing, the language of design is modeled computationally through latent semantic analysis (LSA), lexical chain analysis (LCA), and sentiment analysis (SA). The statistical co-occurrence of semantics (LSA), semantic relations (LCA), and semantic modifiers (SA) in design text are used to illustrate how the reality producing effect of language is itself an enactment of design. This insight leads to a new understanding of the connections between creative behaviors such as design and their linguistic properties. The computation of the language of design makes it possible to make direct measurements of creative behaviors which are distributed across social spaces and mediated through language. The book demonstrates how machine understanding of design texts based on computation over the language of design yields practical applications for design management such as modeling teamwork, characterizing the formation of a design concept, and understanding design rationale. The Language of Design: Theory and Computation is a unique text for postgraduates and researchers studying design theory and management, and allied disciplines such as artificial intelligence, organizational behavior, and human factors and ergonomics.